2007
DOI: 10.1134/s0021364007140093
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoelectric control of domain walls in a ferrite garnet film

Abstract: The effect of magnetic domain boundaries displacement induced by electric field is observed in epitaxial ferrite garnet films (on substrates with the (210) crystallographic orientation). The effect is odd with respect to the electric field (the direction of wall displacement changes with the polarity of the voltage) and even with respect to the magnetization in domains. The inhomogeneous magnetoelectric interaction as a possible mechanism of the effect is proposed. DOI: 10.1134/S0021364007140093The last few ye… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
88
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 17 publications
(26 reference statements)
0
88
0
Order By: Relevance
“…Like the Dzyaloshinskii-Moriya-like exchange (1a), this inhomogenous interaction is magnetoelectric in origin and a spin cycloid is only possible in the presence of spontaneous polarization. It is remarkable that inhomogenous magnetoelectric interaction (2) can explain magnetoelectric effect in magnetic domain walls [31][32][33] and ferroelectricity in spiral magnets [34] under the assumption of polarization induced by magnetic inhomogeneity. Furthermore, there is a profound analogy between spatially modulated spin structures in multiferroics, and spatially modulated structures in nematic liquid crystals [35,36].…”
Section: Fig 3 Experimental Evidences For Spin Cycloid Existence: (Amentioning
confidence: 99%
“…Like the Dzyaloshinskii-Moriya-like exchange (1a), this inhomogenous interaction is magnetoelectric in origin and a spin cycloid is only possible in the presence of spontaneous polarization. It is remarkable that inhomogenous magnetoelectric interaction (2) can explain magnetoelectric effect in magnetic domain walls [31][32][33] and ferroelectricity in spiral magnets [34] under the assumption of polarization induced by magnetic inhomogeneity. Furthermore, there is a profound analogy between spatially modulated spin structures in multiferroics, and spatially modulated structures in nematic liquid crystals [35,36].…”
Section: Fig 3 Experimental Evidences For Spin Cycloid Existence: (Amentioning
confidence: 99%
“…The magnetooptical technique in Faraday geometry was used to observe the micromagnetic structure (the experimental details are described elsewhere [4]). We registered the magnetization distribution in initial state and the position of domain wall with static 3 Author to whom any correspondence should be addressed. 1) and did not depend on the magnetic polarity of the domain over which the tip was located.…”
Section: Methodsmentioning
confidence: 99%
“…However the spin transfer also requires large current densities of 10 6 -10 7 A/cm 2 . In [3,4] we proposed the new approach to the problem of electrically controlled magnetic state: the electric field driven domain wall motion. It was implemented in epitaxially grown single crystal iron garnet films at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical methods to study the effect of electric fields on dynamical magnetic properties in magneto-electric materials are being developed [Fischbacher 2011], and it has also been shown that dynamical effects such as domain-wall motion can be modified via electric control of intrinsic magnetic properties [Lahtinen 2012, van deWiele 2014 and ferrite garnet films [Logginov 2007]. Recently, magnetization switching due to picosecond electric field pulses in MgO/FePt/Pt(0 0 1) films has been predicted using first principle and micromagnetic simulations [Zhu 2014].…”
Section: Introductionmentioning
confidence: 99%